2019
DOI: 10.1089/bfm.2018.0232
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of a Model Human Immunodeficiency Virus Target by Human Breast Milk Leukocytes Is Predominantly Granulocyte-Driven When Elicited by Specific Antibody

Abstract: Background: Studies demonstrate a protective effect of antibodies (Abs) in breast milk (BM) against motherto-child transmission (MTCT) of human immunodeficiency virus (HIV). Contribution of the BM cellular component has been overlooked. The only clinical HIV vaccine trial to demonstrate efficacy, RV144, correlated protection with Abs mediating functions through the constant immunoglobulin region-the crystallizable fragment (Fc). These data support induction of vaccine Abs triggering antiviral activities by leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 65 publications
(96 reference statements)
2
4
0
Order By: Relevance
“…In the present study, granulocytes were the most potently induced phagocyte against the virus target for most IgG isotypes, consistent with our previous findings using bead-based targets (32).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, granulocytes were the most potently induced phagocyte against the virus target for most IgG isotypes, consistent with our previous findings using bead-based targets (32).…”
Section: Discussionsupporting
confidence: 93%
“…We have undertaken a study to assess the ADCP capacity of human milk leukocytes against HIV. Our previous pilot study confirmed milk leukocytes as capable of ADCP of HIV Env gp120-coated microbeads, and demonstrated that most activity was granulocyte-driven (31,32).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…We have undertaken a study to assess the ADCP capacity of human milk leukocytes against HIV. Our previous pilot study confirmed milk leukocytes as capable of ADCP of HIV Env gp120-coated microbeads, and demonstrated that most activity was granulocyte-driven ( 40 , 41 ). In the present study we report our analysis of the ADCP activity of milk leukocytes in 57 unique samples from 34 women, elicited by recombinant IgG1/2/3/4 of monoclonal (m)Ab 246-D, a weakly-neutralizing Env gp41 (cluster 1)-specific Ab - the type of Ab commonly elicited by natural HIV infection.…”
Section: Introductionmentioning
confidence: 70%
“…This primary milk cell assay was adapted from Ackerman et al. ( 47 ) and has been described previously using latex beads ( 41 ). Milk samples were centrifuged at 600 g for 15 min, cell pellet was washed 2x with Hank’s balanced salt solution (HBSS) without calcium and magnesium with centrifugation at 350g for 10 min.…”
Section: Methodsmentioning
confidence: 99%